Legionella Persistence in Manufactured Water Systems: Pasteurization Potentially Selecting for Thermal Tolerance - Whiley, Harriet; Bentham, Richard; Brown, Melissa H. (Frontiers in Microbiology, 2017)
Legionella is an opportunistic waterborne pathogen of increasing public health significance. Pasteurization, otherwise known as super-heat and flush (increasing water temperature to above 70oC and flushing all outlets), has been identified as an important mechanism for the disinfection of Legionella in manufactured water systems. However, several studies have reported that this procedure was ineffective at remediating water distribution systems as Legionella was able to maintain long term persistent contamination. Up to 25% of L. pneumophila cells survived heat treatment of 70oC, but all of these were in a viable but non-culturable state. This demonstrates the limitations of the culture method of Legionella detection currently used to evaluate disinfection protocols. In addition, it has been demonstrated that pasteurization and nutrient starvation can select for thermal tolerant strains, where L. pneumophila was consistently identified as having greater thermal tolerance compared to other Legionella species. This review demonstrates that further research is needed to investigate the effectiveness of pasteurization as a disinfection method. In particular, the potential for pasteurization to select for thermal tolerant L. pneumophila strains which have greater public health significance compared to other Legionella species.